Character Education Models at School - Yusella, Yeni; Sultoni , Achmad; Suciptaningsih, Oktaviani Adhi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The purpose of writing this article is to find out the concept of character education formulated by experts, the scope of character education in  detail, and  character education  in terms of  the  scope of character education .  The research conducted uses a descriptive analytical method, namely by describing theories according to experts about character education .  From the research conducted, it was concluded  that the  emergence of character education  actually showed  more of  the characters that must be possessed by every  student and at the same time the  character education   strengthened  religious education.  Character education produce students into creatures who have better characters or values.  The success of character education does not depend on whether or not one of the components of education is good or  not but rather   each   other is interrelated  and inseparable,  so that comes to what  is formulated in the  purpose of character  education. There are some character education learning model  inspired by Religious education  theory, namely: there are three models of character  education, namely "(1)  Tadzkirah Model, (2)  Istiqomah Model, and (3) Iqra- Fikir – Dzikir Model ". Character education can be instilled through a holistic education model covering 3 (three) domains, namely; (1) knowing the good method, (2) feeling the good, and (3) acting the good.